Phonetic Proficiency in /r/ Pronunciation: A Case Study of Chinese Students Learning Indonesian - Arifin, Muhammad Nur; Wiranota, Hesti (Linguistics and ELT Journal, 2023)
In the realm of BIPA (Bahasa Indonesia untuk Penutur Asing) learning, learners grapple with a myriad of challenges, chief among them being the linguistic disparities between their native language (L1) and the target language (L2) they are striving to acquire. Mandarin Chinese, in particular, presents a unique challenge due to its partial incorporation of the /r/ sound, albeit to a lesser extent compared to Indonesian, and its distinct articulation, which varies markedly from other languages. Moreover, the pronunciation of this sound can differ among various Chinese dialects, adding an additional layer of complexity for Chinese learners of Indonesian. This study pursues three primary objectives: (1) the identification of sound changes in the /r/ sound; (2) the classification of the various types of sound changes affecting the /r/ sound; and (3) the identification of common sound changes associated with the /r/ sound within this specific learner group. To achieve these aims, a quantitative descriptive analysis methodology was employed. The research data were collected through voice recordings of 16 students enrolled in the fifth semester of the undergraduate program in Indonesian Studies at Zhejiang Yuexiu University of Foreign Languages, China. The results of the study unveiled a spectrum of phonetic proficiency levels and challenges among the participants. Notably, 75% of respondents demonstrated accurate pronunciation of the /r/ sound, showcasing a high level of proficiency in this aspect of their language acquisition. However, 15% exhibited a tendency to replace the sound with /l/, highlighting a specific area that requires targeted pedagogical interventions. Additionally, 5% grappled with zeroization, completely omitting this sound, underscoring the necessity for focused language instruction. In only 1% of instances, respondents produced words that were unidentifiable due to potential omissions, necessitating further investigation. Further research is strongly encouraged to explore the effectiveness of customized phonetic training programs and their correlation with learners' linguistic backgrounds in shaping pronunciation proficiency among Chinese students studying Indonesian.